Feasibility and predictors of early discharge after percutaneous edge-to-edge mitral valve repair. Issue 12 (9th January 2017) - Tamburino, Corrado; Buccheri, Sergio; Popolo Rubbio, Antonio; Scandura, Salvatore; Di Salvo, Maria Elena; Mangiafico, Sarah; Immé, Sebastiano; Caruso, Giuseppe; Scalia, Matteo; Condorelli, Antonio; Barbanti, Marco; Capranzano, Piera; et al.
Abstract : Background: Percutaneous edge-to-edge mitral valve repair (PMVR) recently emerged as an effective treatment modality for patients with severe mitral regurgitation (MR). Length of postprocedural hospital stay may represent a modifiable cost associated with percutaneous treatment. We looked at feasibility, predictors and safety of early discharge (ED), defined as hospital discharge within 72 hours, in patients undergoing PMVR. Methods and results: Consecutive patients treated with MitraClip from October 2008 to December 2015 were analysed. Primary outcomes of interest were cardiovascular and non-cardiovascular mortality, rehospitalisation for heart failure and major adverse events at 30 days and 90 days. A total of 269 patients were included. Of these, 115 patients were early discharged (ED group). Rates of ED increased from 25.9% for the biennium 2008–2009 to 59.1% in 2014–2015 (p<0.001 for trend). In a penalised logistic regression model, male gender (OR=2.13, 95% CI 1.17 to 3.95) and procedural year (OR=2.13, 95% CI 1.51 to 3.11) were associated with higher probability of ED. Conversely, atrial fibrillation (OR=0.48, 95% CI 0.27 to 0.85), any Mitral Valve Academic Research Consortium bleeding (OR=0.07, 95% CI 0.01 to 0.60), log-transformed N-terminal pro-brain natriuretic peptide levels (OR=0.79, 95% CI 0.63 to 0.99) and postimplant MR grade (OR=0.60, 95% CI 0.37 to 0.94) conferred a lower likelihood of ED. In propensity score-weighted analyses, overall survival, freedom from heart failure and major adverse events at 30 days and 90 days were not different in ED and non-ED groups (all weighted log-rank p value>0.05). Conclusions: In selected patients undergoing PMVR, ED may be feasible and safe.